Modernization of traditional Malay house in heritage village of Malacca / Rohaslinda Ramele, Yasmin Nur Amirah Yaman and Nor Rima Muhammad Ariff - Ramele, Rohaslinda; Yaman, Yasmin Nur Amirah; Muhammad Ariff, Nor Rima (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2021)
Traditional Malay house is undergoing a lot of changes and threatened by modernization where its function, form and structure are affected. A lot of traditional Malay houses today are not considered as original vernacular houses where they are transformed and modernized into mixed design types between traditional and recent modern design. This paper aims to clarify modernization and alteration done, and new internal usage of selected four traditional Malay houses in two heritage villages: Kampung Banda Kaba and Kampung Sidang Seman, in Malacca. Interviews and field investigations were carried out at the selected houses that chosen based on the existing of original structure such as rumah ibu, rumah dapur and raised floor. Findings showed that all four traditional Malay houses had created a new usage style where the owners had altered and extend their houses based on their current needs and lifestyles.